OPTIMALISASI BUDAYA MUTU SEKOLAH UNTUK MENINGKATKAN KOMITMEN GURU - Rais Hidayat; Henny Suharyati; Yuyun Elizabeth Patras; Sutji Harjanto; Haposan Andi (Universitas Pakuan, 2018)
Teacher's commitment is the key to improve education. The purpose of this research is to investigate the efforts to increase teacher commitment through quality culture in schools. Based on 110 samples involved this research, it is found that the improvement of teacher commitment can be achieved by optimizing the quality culture in schools. The optimization of the quality culture in schools can be achieved through several ways: the fulfillment of infrastructure; internal and external customer satisfaction; development of teacher professionalism; team work; collaboration with other parties (parents, school board, and society); school evaluation and determination of reward and punishment.Keywords: teacher's commitment, quality culture, education.